Enrichment of fresh pasta with beta-carotene from tiessa (Pouteria campechian) fruit - Bughao, Rachelle Ann Betiwan (2009.)
Enrichment of fresh pasta with B-carotene using tiessa (Pouteria campechian) fruit was done.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Tiessa; Beta-carotene.